PIT AND FISSURE SEALANTS IN CARIES PREVENTION: MATERIALS, CLINICAL EFFECTIVENESS, AND MODERN APPROACHES (International journal of artificial intelligence, 2026)
Pit and fissure sealants are widely recognized as an effective preventive measure against occlusal caries, particularly in children and adolescents. Due to the complex morphology of occlusal surfaces, these areas are highly susceptible to plaque accumulation and demineralization. This review aims to evaluate the clinical effectiveness of different sealant materials, application techniques, and recent advancements in sealant technology. The findings indicate that proper application and material selection significantly influence long-term retention and caries prevention. Modern developments, including bioactive and antimicrobial sealants, offer additional benefits and may enhance clinical outcomes.